DAMPAK DIBATALKANNYA UNDANG-UNDANG NOMOR 7 TAHUN 2004 TENTANG SUMBER DAYA AIR TERHADAP MANAJEMEN AIR UNTUK KESEJAHTERAAN MASYARAKAT - Sudarwanto, AL. Sentot (Yustisia, 2015)
AbstractThe water power resource has a great role to support the activities in the fields of farming, clean water of urban and rural areas, industries, fish embankments, tourisms, electricity power, and flood and erosion controls. Based on the Law No 7 Year 2004 on the Water Power Resource, it has been given the usage right of water management widely to the privates to join to manage the water power resource, which, then, results the understanding of social function and economical function and raising the efforts of private enterprise and commercialization of the water power resource which inflicted a loss up on the public. Based on this consideration, the Constitution Court abrogated the validity of the Law of SDA (Water Power Resource) on the whole and put into effect the Law Number 11 Year 1974 on Irrigation and the Government Regulation Number 22 Year 1982 on the Water Regulation Management. The abrogation will cause impacts to the government (executive), the Corporation of Water Management, and Society. The State should fulfill the people’s right on water considering that the society’s access to water is one of the Basic Human Rights. The prominent priority authority on water should be given to BUMN and BUMD as the follow up of the right authorization by the State on water. The private element may be allowed to carry out to authorize on water with strictly specific requirements. The water usage should consider the function of environmental conservation. The direct impact is that the Government, in the near future, has no Law / Regulation protection to carry out the management of SDA (Water Power Resource) in the field, since all management regulations as the copy of the Law of the Resource of Water Power had also been abrogated. Therefore, the regulation has to be issued soon. The government should prepare the draft of the Government Regulation Planning based on the Law Number 11 Year 1974 and the Law Planning on the Water Power Resource (to substitute Law No 11 Year 1974). The three important substances that must be included are the conservations of water power resource, the usage of water power resource and the control of water damaging power. AbstrakSumberdaya air mempunyai peran cukup besar dalam menunjang kegiatan bidang pertanian, air bersih perkotaan dan pedesaan, industri, perikanan tambak, pariwisata, tenaga listrik, dan pengendalian banjir serta erosi. Berdasarkan UU No 7 tahun 2004 tentang Sumber Daya Air telah memberikan hak guna usaha air secara luas kepada swasta untuk ikut mengelola sumberdaya air, sehingga muncul pemahaman terhadap fungsi social dan fungsi ekonomi serta terjadinya usaha privatisasi dan komersialisasi sumberdaya air yang merugikan masyarakat. Atas pertimbangan ini, Mahkamah konstitusi membatalkan keberlakuan secara keseluruhan UU SDA dan diberlakukannya kembali Undang-Undang Nomor 11 Tahun 1974 tentang Pengairan dan Peraturan Pemerintah Nomor 22 Tahun 1982 Tentang Tata Pengaturan Air. Pembatalan UU SDA akan menimbulkan dampak bagi pemerintah (eksekutif), Badan Usaha pengelola Air, dan Masyarakat. Negara harus memenuhi hak rakyat atas air mengingat akses masyarakat terhadap air merupakan salah satu Hak Asasi Manusia. Prioritas utama penguasaan atas air diberikan kepada BUMN atau BUMD sebagai kelanjutan hak menguasai oleh Negara atas air. Unsur swasta masih dimungkinkan melakukan penguasaan atas air dengan syarat-syarat tertentu secara ketat. Pemanfaatan air harus mengingat kelestarian fungsi lingkungan hidup. Dampak langsung adalah bahwa pemerintah dalam waktu dekat tidak mempunyai paying hukum untuk melaksanakan pengelolaan SDA di lapangan,karena semua aturan pelaksanaan sebagai turunan dari UU SDA juga dibatalkan. Oleh karena itu aturan payung hukum harus segera diterbitkan. Pemerintah segera menyiapkan draf Rancangan Peraturan Pemerintah (RPP) yang berpijak pada UU Nomor 11 Tahun 1974 dan Rancangan Undang-Undang (RUU) tentang Sumber Daya Air (pengganti UU No 11 Tahun 1974). Tiga substansi penting yang harus dimuat yaitu konservasi sumberdaya air, pendayagunaan sumberdaya air dan pengendalian daya rusak air